2016
DOI: 10.1016/j.avb.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Martial arts participation and externalizing behavior in juveniles: A meta-analytic review

Abstract: Martial arts are very popular among juveniles all over the world, but the relation between martial arts and externalizing behavior in juveniles remains unclear. The current multilevel meta-analysis of 12 studies, including 94 effect sizes and N = 5949 juveniles, was conducted to examine the relation between martial arts participation and externalizing behavior in juveniles, and to examine factors with a possible moderating effect. Results showed that there was no overall relation between martial arts participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 51 publications
2
23
0
7
Order By: Relevance
“…These anxiogenic levels may vary depending on the situation. 20 Therefore, it has been demonstrated that there should be an ideal level of anxiety for each athlete, considering that the state of intensity should be compatible with the nature of the activity, so that favorable results can be obtained. 17 In this sense, high-performance boxing athletes in Brazil should not only enjoy physical, technical, tactical, nutritional, and medical preparation, but also psychological 16 preparation.…”
Section: Discussionmentioning
confidence: 99%
“…These anxiogenic levels may vary depending on the situation. 20 Therefore, it has been demonstrated that there should be an ideal level of anxiety for each athlete, considering that the state of intensity should be compatible with the nature of the activity, so that favorable results can be obtained. 17 In this sense, high-performance boxing athletes in Brazil should not only enjoy physical, technical, tactical, nutritional, and medical preparation, but also psychological 16 preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, because martial art training is one of the most popular sports activities among adolescents in the West [Gubbels et al 2016], learning how to teach and guide, through one's body, developing an ethics of care (in which helping others develop skills is a central goal) can significantly and positively calibrate masculinity. Martial arts can serve as an arena in which certain forms of touch can be interpreted as reassuring, or part of a learning experience, etc., rather than as sexual, or arousing, or homophobic, etc.…”
Section: Fighting Gender Stereotypesmentioning
confidence: 99%
“…Although evidence on the benefits of martial arts study is ample in the literature, research examining martial arts as interventions for violence, aggression, and bullying is sparse and inconsistent. Some evidence suggests no significant association between martial arts participation and juvenile anger and aggression (Gubbels, van der Stouwe, Spruit, & Stams, 2016), while other research indicates that martial arts are associated with higher levels of anger and violence (Lotfian, Ziaee, Amini, & Mansournia, 2011;Mutz, 2012;Ziaee, Lotfian, Amini, Mansournia, & Memari, 2012). Still other research asserts that martial arts are associated with decreased externalizing behaviors (Harwood, Lavidor, & Rassovsky, 2017;Twemlow et al, 2008;Vertonghen & Theeboom, 2010).…”
Section: Martial Arts As An Interventionmentioning
confidence: 99%
“…Type of martial arts studied may be another moderating factor in the association with aggression and violence. Classical martial arts styles such as karate have traditionally been associated with less aggression than boxing or judo (Gubbels et al, 2016), Further, Milligan et al (2017 found that when integrated with mindfulness approaches, such as increased acceptance of the present moment as well as awareness of thoughts and bodily sensations, even mixed martial arts (MMA)traditionally viewed as an aggressive style of martial arts-was associated with social and emotional benefits (Milligan et al, 2017).…”
Section: Moderating Factorsmentioning
confidence: 99%